Bioenergetic status and hypoxia in Lewis lung carcinoma assessed by 31P NMR spectroscopy: correlation with tumor progression - Bubnovskaya, L.; Mikhailenko, M.; Kovelskaya, A.; Osinsky, S. (Experimental Oncology, 2007)
Aim: Тo evaluate the hypoxia level and some indices of Lewis lung carcinoma energy metabolism by means of 31Р NMR spectroscopy in perchloric acid (PCA) tissue extracts during growth of primary tumor and metastasis. Мaterials and Methods: C57Bl/6 mice-bearing Lewis lung carcinoma were used in this study. Tumor energy metabolism was studied by 31P NMR spectroscopy and the metabolic NMR ratios were used as parameters for metabolic status and hypoxia level. Results: It was shown that growth of primary tumor is accompanied with increase of Pi/PCr, Pi/bNТP and PME/bNТP ratios that reflect drop of tumor energy status and oxygenation level in tumor tissue. These changes in relevant metabolic ratios correlate with enlargement of primary tumor volume (r = 0.87, p = 0.0045; r = 0.90, p = 0.0012; r = 0.764, p = 0.05, respectively) as well as with the number of lung metastases (rs = 0.761, p = 0.028; rs = 0.86, p = 0.0049; rs = 0.77, p = 0.040, respectively). Conclusion: In present study it was shown that 31Р NMR spectroscopy of PCA tumor tissue extracts may be used as reliable method for the assessment of the level of oxygenation as well as changes in energy metabolism in the experimental tumors. It may be helpful to evaluate the energy status of human tumors by investigation both of biopsy and surgical specimens. Hypoxia and hypoxia-associated metabolic events in primary tumor are linked with malignant progression, in particular metastasis.